Public-private partnerships: origin, limitations and prospects for public sector accounting - Matos, Nyalle Barboza; Gonçalves, Andréa de Oliveira (Revista Eletrônica de Administração, 2020)
The main objective of this research is to identify and discuss theoretically the advances, limitations and perspectives pointed by international research to improve the accountability and evaluation aspects of PPPs. This is a theoretical essay based on the Public Choice Theory to show that the PPP accounting treatment is relevant to avoid lack of transparency and accountability, mitigating possible losses in the decision making process and the ineffective allocation of public resources. The discussion of topics reveals the importance of public accounting in measuring the financial and social consequences that the shared responsibility of PPPs can have., defending the public interest and democratic relations. It is argued that different factors may influence PPP accounting issues, involving governance limitations, institutional weaknesses, widespread corruption, lack of transparency, weak regulatory environments, power imbalances between partners, lack of political commitment and trust. Finally, some accounting research questions and topics are presented that should be considered to prevent private interest from overriding the public interest in contracting a PPP.